RF and Microwave Module Level Design and Integration - Almalkawi, Mohammad (The Institution of Engineering and Technology, 2019)
This book is intended to bring together fundamental concepts and elements needed in the design, integration, and characterization phases of modern radio frequency (RF) and microwave modules and to familiarize the interested reader with the common challenges in this rapidly changing field. While design for manufacturability (DFM) and design for testability (DFT) are two important practices that stress the need for careful attention at the early design stages of a product, module integration to achieve optimal RF performance is an art form that takes years to master. In this context, the objective of this book is to provide the necessary practical and theoretical background needed to tackle a multitude of issues accompanied by the design of contemporary RF modules. The topics covered can serve a broad range of individuals: those just entering the field, graduate-level students, and researchers, as well as practicing engineers seeking new domains to expand their knowledge, understand design tradeoffs, and looking for a quick guide in digesting the several aspects of the RF module design processes and their common challenges. The book comprises eight chapters which discuss: packaging, lumped and distributed passive elements, microwave network analysis, impedance matching networks, electromagnetic field couplings, CAD, components of RF front-end modules, component- and module-level measurements.
Keywords: Computer-aided design.; Electric circuits.; Electric networks, Passive.; Electronic circuit design.; Electronic packaging.; Impedance matching.; Lumped elements (Electronics); Microwave circuits.; elektronické knihy; electronic books